THE EFFECT OF WATERSHED ENVIRONMENTAL CONDITIONS AND LANDUSE ON SEDIMENT YIELD IN ALO-POHU WATERSHED - Fitryane Lihawa; Sutikno . (Faculty of Geography, Universitas Gadjah Mada, 2009)
The research carried out in alo-pohu watershed gorontalo province aims atidentifying the effect of watershed conditions and land use on the amount sheeterosion, sediment yield and sediment delivery ratio. It is also intended to developthem in a spatio-temporal distribution, and give recommendation for managementof environmental condition and land use in alo-pohu watershed to prevent damageerosion and sediment. Data on environmental condition and land use werecollected by interpreting landsat images and topography map. Data on surfaceerosion were obtained by means of direct measurement using 10 erosion plotsplaced in the land units. Data on sediment were obtained by collecting watersamplesfrom the upper course, middle course, and lower course of the rivers. Dataon sheet erosion and.sediment yield were analyzed in a spatio-temporal mannerusing geographic information systems (gis) and effect of watershed conditions andland utilization on sheet erosion, sediment yield, and sediment delivery ratio aretested using double regression analysis. The research results suggest significanteffect of watershed conditions and land use on sheet erosion. the largest amount oferosion very likely occurred in wasteland (bero land) with steep slopes whereas theleast amount of erosion was found in undergrowth with flat slope (0-8%). theamount of sheet erosion was 122.24 ton/ha/year. sediment yield in alo-pohu wasaffected to a large extent by runoff rate, the width of watershed, percentage ofwasteland, and drainage density.